THE IMPACT OF INTERNET ADDICTION ON THE ESTABLISHMENT OF URBAN CULTURE IN RURAL ADOLESCENTS (RELIGIOUSNESS AND SELF-CONTROL FACTORS ANALYSIS) - Puspitasari, Rini; Riadi, Dayun (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2023)
The phenomenon of internet addiction among rural youth is one of the factors that affect psychosocial and mental health. Intervention is required to help rural adolescents who are addicted to the Internet become more accountable for their responsibilities in life. Efforts to prevent Internet addiction need careful consideration of the conceptual selection of assessments to guide therapies and quantify the influence of Internet addiction's degree of self-control and religion. As a result, the supplied intervention is anticipated to combat internet misuse, which causes rural adolescents to abandon their obligations. Research that focuses on the level of self-control and religiosity in influencing rural youth internet addiction. This research uses a descriptive quantitative approach with multiple regression analysis. This study involved 376 youth aged 14 to 20 years in Bengkulu Province, with 200 male and 176 female participants. The data collection technique uses a scale of religiosity and internet addiction. The results of this study have identified the level of self-control and religiosity influencing internet addiction in rural adolescents. Thus, it can be concluded that religiosity can be used as a basis for practitioners to implement appropriate interventions by looking at the level of self-control to overcome the problem of internet addiction among rural youth by understanding and encouraging adolescents to behave according to levels of obedience, belief, and ethics.